2020
DOI: 10.1038/s41540-020-00156-4
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria interaction networks show altered topological patterns in Parkinson’s disease

Abstract: Mitochondrial dysfunction is linked to pathogenesis of Parkinson’s disease (PD). However, individual mitochondria-based analyses do not show a uniform feature in PD patients. Since mitochondria interact with each other, we hypothesize that PD-related features might exist in topological patterns of mitochondria interaction networks (MINs). Here we show that MINs formed nonclassical scale-free supernetworks in colonic ganglia both from healthy controls and PD patients; however, altered network topological patter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 65 publications
(96 reference statements)
0
7
0
Order By: Relevance
“…Mitochondrial morphometrics were quantified as previously described. 19 Additional data on mitochondrial network can be consulted in Zanin et al 20…”
Section: Live Cell Imaging and Analysismentioning
confidence: 99%
“…Mitochondrial morphometrics were quantified as previously described. 19 Additional data on mitochondrial network can be consulted in Zanin et al 20…”
Section: Live Cell Imaging and Analysismentioning
confidence: 99%
“…This unbiased and data-driven study provided a foundational resource for the PD community through a publicly available pathways browser. Pathways previously implicated by genetics and functional studies also found to be significant in this study include endocytic trafficking [ 61 , 62 ], autophagic-lysosomal function [ 51 , 63 ], mitochondrial function [ 64 , 65 ], protein aggregation [ 66 ], neuronal transmission [ 67 ], lipid metabolism [ 68 , 69 ], and certain inflammatory pathways [ 70 , 71 ] ( Figure 1 ). It has also been shown that similar pathways can be deficient in both familial and common forms of PD [ 51 , 62 ] and multiple networks can overlap or a single pathway can act alone.…”
Section: Genetics As a Tool To Nominate Network To Be Targeted Inmentioning
confidence: 72%
“…Assessment of the endogenous p.A53T SNCA expression in dopaminergic neurons against their isogenic gene corrected control have identified mitochondrial dysfunction and apoptosis from increased basal levels of oxidative and nitrosative stress 55 , reductions in neurite length and complexity 53 , and impaired mitochondria dynamics 64 . Upregulation of ER stress and activation of the unfolded protein response pathway have been found neurons in a triplication of the SNCA gene dosage 63 , and we previously reported that gene-correction of the A30P mutation rescues the mitochondrial interaction network 35 .…”
Section: Discussionmentioning
confidence: 84%
“…To control for the influence of the genetic background we assessed the bioenergetic profile of neurons directly differentiated from two different iPS clones carrying the A30P mutation, which we have previously characterised 34 . Comparing these pathological neurons against neurons from an age- and gender-matched non-PD control 35 , we find that the bioenergetic profile of both clonal cell lines carrying the A30P alpha-synuclein mutation align, with mitochondrial respiration and ATP production significantly reduced compared to the control. To further investigate the loss of ATP, we assessed the mitochondrial membrane potential (MMP) of the neurons containing the A30P mutation against gene-corrected neurons, and to control for the genetic background, a gender-matched non-PD control that we have also previously characterised 32 , finding that in the pathological neurons MMP is reduced (Supp.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation